Seignorage Wealth in the Eurosystem: Eurowinners and Eurolosers Revisited - Hans-Werner Sinn; Holger Feist (Center for Economic Studies and ifo Institute (CESifo), 2000)
The rules laid down in Article 32 of the Protocol No. 18 on the Statute of the European System of Central Banks and of the European Central Bank of the Maastricht Treaty will significantly redistribute European seignorage income and hence the implicit entitlement to the 352 billion stock of interest bearing assets which the central banks contributed to the currency union as of 1 January 1999. According to current plans, the redistribution will start by 1 January 2002. In terms of wealth equivalents and anticipating the Greek participation, Germany will lose 30 billion (or 59 billion deutschmarks) and France will gain 31 billion (or 202 billion French francs). Portugal will gain 3.9 billion (or 792 billion escudos) and Spain will lose 11 billion (or 1 879 billion pesetas). In per capita terms, Luxembourg, Finland and France will be the main winners with gains of 1 309, 627 and 527, respectively, whereas a German will lose 366 and a Spaniard 287. The paper argues that this redistribution was not intended by the signing parties and recommends a revision of the Maastricht Treaty to correct the mistake.
Keywords: 330; Central banks; European integration; European Monetary Union; seignorage